COMMUNICATION STRATEGIES OF VILLAGE GOVERNMENT IN MANAGING CONFLICTS OVER BEACH ENTERTAINMENT ACTIVITIES - Hamdan Febrian Ilham Yahya; Iman Sumarlan (RADJA PUBLIKA, 2026)
This study is motivated by the social dynamics arising from entertainment activities at Tirta Samudra Beach, Bandengan Village, Jepara Regency, which have triggered local community complaints concerning noise, traffic congestion, waste accumulation, and concerns over potential shifts in social and cultural values. These conditions require the Bandengan Village Government to develop adaptive communication strategies to balance the economic benefits of tourism with the comfort and order of local residents. The aim of this research is to analyze the communication strategies implemented by the village government in responding to community complaints, including their effectiveness, challenges, and broader implications. This study employs a qualitative descriptive approach with a case study design, utilizing in-depth interviews, participatory observation, and document analysis. The findings indicate that the village government applies dialogical and participatory communication strategies through village meetings, policy socialization, the use of both conventional and digital media, and the development of persuasive and empathetic messages. These strategies have proven effective in reducing potential conflicts and fostering public trust, although several obstacles remain, such as limited human resources, unequal access to information, and differing interests among stakeholders. The study emphasizes that strategic communication plays a crucial role as an instrument for social harmony, public participation, and sustainable village development. The results are expected to provide practical recommendations for village governments and tourism managers facing similar social dynamics.